Experimental study of a wet mix shotcrete for primary tunnel linings—Part II: Shrinkage, creep, thermal and hygral behavior of shotcrete. (15th May 2022) - Smaniotto, S.; Neuner, M.; Cordes, T.; Hofstetter, G.
Abstract: Part II of the study of a wet mix shotcrete focuses on creep and shrinkage as well as on the thermal and hygral behavior. It deals with the time-dependent mechanical behavior due autogenous shrinkage, combined autogenous and drying shrinkage, and basic creep and combined basic and drying creep for moderate and high levels of sustained compressive stress, applied at different shotcrete ages. Furthermore, the evolution of the temperature due to hydration and the degree of hydration, the evolution of the porosity and the water content of sealed specimens, and the desorption isotherm are determined, providing additional material data for shotcrete models. Highlights: Evolution of autogenous and total shrinkage strain of wet mix shotcrete. Evolution of basic and total creep strain for moderate and high stress levels. Evolution of the temperature due to hydration and the degree of hydration. Determination of hygral behavior: porosity, water content, and desorption isotherm. Together with Part I, a comprehensive data set for a wet mix shotcrete is provided.